2016
DOI: 10.1007/s00253-016-7320-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evolution of an activator-independent methanol dehydrogenase from Cupriavidus necator N-1

Abstract: Methanol utilization by methylotrophic or non-methylotrophic organisms is the first step toward methanol bioconversion to higher carbon-chain chemicals. Methanol oxidation using NAD-dependent methanol dehydrogenase (Mdh) is of particular interest because it uses NAD(+) as the electron carrier. To our knowledge, only a limited number of NAD-dependent Mdhs have been reported. The most studied is the Bacillus methanolicus Mdh, which exhibits low enzyme specificity to methanol and is dependent on an endogenous act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 40 publications
3
92
0
Order By: Relevance
“…Strain Ho1‐7 was identified as Cupriavidus necator (100% 16S rRNA gene identity with C. necator N‐1 T ), for which its methylotrophy was unknown (Makkar and Casida, ). Wu and colleagues () reported that C. necator N‐1 possessed a NAD‐dependent MDH to oxidize methanol, but it does not utilize methanol as a carbon source in the absence of La 3+ . However, the genome of C. necator N‐1 contains a putative xoxF gene (CNE_RS23020; CP002878; Poehlein, et al ., ), which indicates that C. necator N‐1 may be a La 3+ ‐dependent methylotroph.…”
Section: Resultsmentioning
confidence: 99%
“…Strain Ho1‐7 was identified as Cupriavidus necator (100% 16S rRNA gene identity with C. necator N‐1 T ), for which its methylotrophy was unknown (Makkar and Casida, ). Wu and colleagues () reported that C. necator N‐1 possessed a NAD‐dependent MDH to oxidize methanol, but it does not utilize methanol as a carbon source in the absence of La 3+ . However, the genome of C. necator N‐1 contains a putative xoxF gene (CNE_RS23020; CP002878; Poehlein, et al ., ), which indicates that C. necator N‐1 may be a La 3+ ‐dependent methylotroph.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, their performance in platform microorganisms such as Escherichia coli is unsatisfactory . In addition to the activator‐dependent Mdhs, two activator‐independent Mdhs from Geobacillus stearothermophilus DSM 2334 and Cupriavidus necator N‐1 have been reported and characterized . Among all the reported Mdhs, Mdh from G. stearothermophilus DSM 2334 was proven to possess comparably higher V max and lower K M values towards methanol and work better in synthetic methylotrophs .…”
Section: Resultsmentioning
confidence: 99%
“…A key factor that affects the efficiency of methanol bioconversion is the balance between formaldehyde generation and consumption. Currently, all NAD‐dependent Mdhs suffer from low catalytic efficiency . The formaldehyde reduction activity of NAD‐dependent Mdh is at least 1000‐fold higher than methanol oxidation activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have also been reported in other model organisms such as Corynebacterium glutamicum, Pseudomonas putida and Saccharomyces cerevisiae (as reviewed recently by (Heux S. et al, 2018)). Improvements in methanol assimilation have been achieved using different strategies such as (i) optimizing the cultivation medium (Gonzalez et al, 2018), (ii) lowering the thermodynamic and kinetic constraints associated with NAD-dependent methanol oxidation (Roth et al, 2019; Wu et al, 2016), (iii) improving formaldehyde assimilation (Price et al, 2016; Woolston et al, 2018), (iv) increasing carbon fluxes through the autocatalytic cycle (Bennett et al, 2018), and (v) coupling the activity of the RuMP cycle to the growth of the host microorganism and then using adaptive laboratory evolution (Chen et al, 2018; He et al, 2018; Meyer et al, 2018). However, none of these synthetic strains are able to grow on methanol alone.…”
Section: Introductionmentioning
confidence: 99%